A case of dropped head syndrome due to focal myositis that worsened with cellulitis and improved only by treatment of cellulitis. (3rd April 2021) - Akiyama, Mitsuhiro; Kaneko, Yuko; Saito, Shuntaro; Matsumoto, Kotaro; Kondo, Yasushi; Hanaoka, Hironari; Otomo, Kotaro; Oyama, Munenori; Matsubara, Shiro; Takeuchi, Tsutomu
Abstract: Dropped head syndrome due to focal myositis is extremely rare. Due to the rarity of the disease, its clinical characteristics and prognosis remain unknown. We present a unique case of dropped head syndrome due to focal myositis that exacerbated following cellulitis and was dramatically improved along with the improvement of her cellulitis only treated with antibiotics. We should consider the possibility of preceding trigger event such as infection when we face with the exacerbation of focal myositis before making a decision of strengthening immunosuppressive therapy to avoid unnecessary increase of glucocorticoid.